Unlocking the potential of Rosa roxburghii Tratt polyphenol: a novel approach to treating acute lung injury from a perspective of the lung-gut axis - Tang, Li; Zhang, Shuo; Zhang, Min; Wang, Pengjiao; Liang, Guiyou; Gan, Zhitong; Gao, Xiuli (Frontiers in Microbiology, 2024)
Acute lung injury (ALI) is a serious respiratory disease characterized by progressive respiratory failure. Rosa roxburghii Tratt polyphenol (RRTP) has significant preventive and therapeutic effects on lipopolysaccharide-induced ALI mice, but its regulatory effects on gut homeostasis in ALI mice remains unclear. This study aims to systematically evaluate the ameliorative effects of RRTP from the perspective of "lung-gut axis" on ALI mice by intestine histopathological assessment, oxidative stress indicators detection and SCFAs production, and then explore the modulatory mechanisms of RRTP on intestinal homeostasis by metabolomics and gut microbiomics of cecal contents. The results showed that RRTP can synergistically exert anti-ALI efficacy by significantly regulating the composition and structure of intestinal flora and modulating disordered intestinal endogenous metabolites. This study provided a breakthrough for the food and healthcare industries to develop products from botanical functional herbs and foods to prevent or alleviate ALI by regulating intestinal flora.